Bentuk Penyajian Rebana Burdah Pada Acara Perkawinan Kecamatan Lubuak Sikarah Kelurahan Tanah Garam Kota Solok - Anju Cantika; Wimbrayardi Wimbrayardi (SENDRATASIK UNP, 2020)
This study aims to identify and explain the form of Rebana Burdah presentation in a wedding ceremony in Nagari Payo, Lubuak Sikarah district, Tanah Garam village, Solok City. It includes the players, the musical instruments used, the songs presented in Rebana Burdah, the time and place of the performance, the costumes, Rebana Burdah art in the procession, and its supporting community. This is a qualitative researchusing a descriptive method. The object of research was the presentation of Rebana Burdah in NagariPayo, Lubuak Sikarah District, Tanah Garamvillage, Solok City. The data were collected through observation, interview, recording, and shooting. The data were processed by using qualitative analysis. From the data analysis, it is found that the presentation of Rebana Burdah in a wedding ceremony in Nagari Payo, Lubuak Sikarah district, Tanah Garam Village, Solok City, consists of at least four people and six people in maximum. The musical instrument used was a tambourine. The song which accompanies the tambourine is read from a bezanji with radat was made by the Rebana group at Surau Rudah. Meanwhile, the position of Rebana Burdah players in the procession is at the back and there is no rule for what costumes should be worn. Tambourine is onekind of musical instrument. Rebana Burdahuses songs from the zanji book accompanied by rebana. In Nagari Payo community, Lubuak Sikarah District, Tanah GaramVillage, Solok City, Rebana Burdahis presented in every traditional ceremony and Islamic religious holiday, and it is especially performed at wedding ceremony. Rebana Burdah is presented at a wedding ceremony and during the procession. It is presented at night while waiting for the groom at house, and it is presented in the day during the procession.